Culture, power and politics in treaty-port Japan, 1854-1899 : key papers, press and contemporary writings - Hoare, James (Renaissance Books, 2018)
"This two-volume collection, supported by an in-depth introduction that addresses origins, actuality, endgame and afterlife, brings together for the first time contemporary documentation and more recent scholarship to give a broad picture of Japan's Treaty Ports and their inhabitants at work and play in the second half of the nineteenth century."--Publisher description